Ekonomi rakyat : antara gagasan dan realita - Suwarto, Yuni; Santoso, Aris; Sekretariat Bina Desa (Jakarta : Sekretariat Bina Desa, 1995)
The marginal position of smaal business, the informal sector, and home-based industries in aindonesia's economy; economic policies; collection of articles
Keywords: Small business -- Indonesia; Cottage industries -- Indonesia; Indonesia -- Economic conditions -- 1945; Indonesia -- Economic policy